Head-to-Head Comparison of Anti-Inflammatory Performance of Known Natural Products In Vitro - Allijn, Iris E.; Vaessen, Stefan F. C.; Quarles van Ufford, Linda C.; Beukelman, Kees J.; de Winther, Menno P. J.; Storm, Gert; Schiffelers, Raymond M. (PLOS ONE, 2016)
Inflammation is an important therapeutic target. Due to their potency, steroidal drugs dominate the current treatment of inflammatory disorders. However, steroidal drugs can also exert a broad range of side effects and appear not always effective. This calls for the development of alternative drugs with a different mechanism of action, which are likely to be found in the field of natural products (NPs). For many NPs strong anti-inflammatory effects have been described, but usually investigating a single compound in a single assay. In this study, eight promising NPs were selected and tested against the strong anti-inflammatory drug prednisolone. For this head-to-head comparison, in vitro assays were used which represent different pathways of the inflammatory response: TNF-α and IL-6 expression by macrophages, IL-8 expression by colon epithelial cells, ROS production in polymorphonuclear leukocytes and platelet activation in whole blood. Performance profiles were established which allowed us to identify curcumin, berberine chloride and epigallocatechin gallate as potential alternatives for prednisolone or other glucocorticoids in inflammation.